Construction and evaluation of type III secretion system mutants of the catfish pathogen Edwardsiella piscicida. Issue 5 (9th February 2018) - Edrees, A; Abdelhamed, H; Nho, S W; Park, S B; Karsi, A; Austin, F W; Essa, M; Pechan, T; Lawrence, M L
Abstract: Catfish is the largest aquaculture industry in the United States. Edwardsiellosis is considered one of the most significant problems affecting this industry. Edwardsiella piscicida is a newly described species within the genus Edwardsiella, and it was previously classified as Edwardsiella tarda . It causes gastrointestinal septicaemia, primarily in summer months, in farmed channel catfish in the south‐eastern United States. In the current study, we adapted gene deletion methods used for Edwardsiella to E. piscicida strain C07‐087, which was isolated from a disease outbreak in a catfish production pond. Four genes encoding structural proteins in the type III secretion system (T3SS) apparatus of E. piscicida were deleted by homologous recombination and allelic exchange to produce in‐frame deletion mutants ( Ep Δ ssaV, Ep Δ esaM, Ep Δ yscR and Ep Δ escT ). The mutants were phenotypically characterized, and virulence and vaccine efficacy were evaluated. Three of the mutants, Ep Δ ssaV, Ep Δ yscR and Ep Δ esaM, were significantly attenuated compared to the parent strain ( p < .05), but Ep Δ escT strain was not. Vaccination of catfish with the four mutant strains ( Ep Δ ssaV, Ep Δ esaM, Ep Δ yscR and Ep Δ escT ) provided significant protection when subsequently challenged with wild‐type strain. In conclusion, we report methods for gene deletion in E. piscicida and development of vaccine candidates derived from a virulent catfish isolate.